Self-Assembly of Dissymmetric Diketopyrrolopyrrole Chromophores - Killalea, Catherine Elizabeth (2021)
The self-assembly of materials to form well defined nanostructures has been shown to be beneficial to charge carrier mobility in organic electronic devices. This thesis aims to study the self-assembly and aggregation properties of novel dissymmetric diketopyrrolopyrrole derivatives. The synthesis, of both symmetric and dissymmetric diketopyrrolopyrrole derivatives, are described and the influence of the N-alkyl chain, incorporation of chiral lactate groups through Mitsunobu reactions and increase in conjugation using Suzuki couplings on the optical and electronic properties of these materials are reported.